TEKNOLOGI PENGOLAHAN AIR GAMBUT MENJADI AIR BERSIH DALAM UPAYA PENGURANGAN KADAR LOGAM DI DAERAH PEDESAAN - Yeza febriani (Universitas Cokroaminoto Palopo, 2020)
A research has been conducted on the processing of peat water into clean water. This processing aims to reduce the metal content in the peat water content. Before treatment, peat water had high levels of iron, manganese and lead of 0.09 Mg / l, 2.76 Mg / l, and 0.17 Mg / l. The metal parameter still exceeds the maximum limit set by PERMENKES RI NO.416 / Menkes / Per / IX / 1990. The processing methodology used is neutralization, aeration and filterization. Neutralization process. The results showed that the manganese and iron parameters decreased, namely manganese from 2.75 Mg / l to 0.5 Mg / l, iron from 0.09 Mg / l to 0.05 Mg / l. Meanwhile, the lead content still has levels that exceed the maximum reference limit, this is due to the use of pipes containing lead elements